Dependence of the Physical and Mechanical Properties of Eco-Leather on the Conditions for the Formation of a Polymer Coating - Yulia Maruschak; Natallia Yasinskaya; Natallia Skobova; Vyacheslav Sergeev (Vestnik of Vitebsk State Technological University, 2023)
Polyurethane-coated fabrics (eco-leather) have become a popular material for the production of clothing and haberdashery. The authors have developed and implemented a technology for applying a polyurethane coating on a woven base at Baranovichi Cotton Production Association. The difference between the newly developed technology for the production of eco-leather and the existing ones is the use of a foamed polyurethane composition. The aim of the work is to determine the dependence of the physical and mechanical properties of eco-leather on the conditions for the formation of a polymer coating (foam ratio and drying time).